The “Africanization” of an African Diaspora Household: Toyin Falola and the Idea of Diasporic Home-Making - Babatunde Jaiyeoba; Adeshina Afolayan (Yoruba Studies Review)
This essay is an exercise in the interrogation of cultural globalization, and how the idea of transnationalism generates identity responses. The authors used the concept of home-making to examine how Toyin Falola deployed an aesthetic sensibility of African art as ideological dynamics for the personalization of his home situated in a suburb in Austin, Texas. The Africanization agenda that the Falola house operationalized points at the critical role that interior decoration can play in African diaspora homes. The project is crucial because it undermines the homogenizing reach of globalization that dislocates the sense of identity of an average African transnational migrant. In the Falola home, we confront an assemblage of aesthetic consciousness, dynamics of Africanity, and identity construction.